Topsoil depth influences the recovery of rupestrian grasslands degraded by mining - Lina Andrade Lobo Rezende; Geraldo Wilson Fernandes; Ramon de Paula Braga; Luiz Eduardo Dias; Vanessa Matos Gomes (Revista Brasileira de Ciência do Solo, 2021)
ABSTRACT Close association of iron mining and ferruginous rupestrian grassland places this ecosystem in a special condition of vulnerability, with a large number of degraded areas requiring restoration. Seedling transplantation and topsoil translocation can be used to recover native vegetation in degraded areas. This study aimed to experimentally test the application of two different topsoil depths (0.20 and 0.40 m) in a degraded area. We assessed the vegetation’s natural recovery and the survival of transplanted native species from rescue operations in four 200 m2 plots established in each topsoil depth. There was no influence of topsoil depth on the plant species survival, while the vegetation cover was greater on the thicker topsoil. However, exotic species with invasive potential contributed substantially to this vegetation cover, requiring management planning. Some planted native species stood out for their survival ability in the topsoil 49 months after planting. Application of 0.20 m topsoil layer showed to be able to provide native species’ natural recovery and survivorship.